2018
DOI: 10.1016/j.jaad.2017.12.027
|View full text |Cite
|
Sign up to set email alerts
|

Fibrous cephalic plaques in tuberous sclerosis complex

Abstract: Two-fifths of FCPs presented on the forehead, with most of the remainder in other locations on the face and scalp. Better recognition of these lesions may lead to earlier diagnosis of TSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 34 publications
2
28
1
5
Order By: Relevance
“…These plaques can also be found in other craniofacial areas. Oyerinde et al (2018) demonstrated in an observational cohort study that 39% of FCPs were found on the forehead, 31% on the scalp, 27% on the face (non-forehead), and 3% on the neck. These characteristic lesions are found in approximately 25% of TSC patients (Jóźwiak et al, 1998;Webb et al, 1996).…”
Section: Facial Angiofibromas and Fibrous Cephalic Plaquesmentioning
confidence: 99%
See 2 more Smart Citations
“…These plaques can also be found in other craniofacial areas. Oyerinde et al (2018) demonstrated in an observational cohort study that 39% of FCPs were found on the forehead, 31% on the scalp, 27% on the face (non-forehead), and 3% on the neck. These characteristic lesions are found in approximately 25% of TSC patients (Jóźwiak et al, 1998;Webb et al, 1996).…”
Section: Facial Angiofibromas and Fibrous Cephalic Plaquesmentioning
confidence: 99%
“…As FCPs are histologically similar to angiofibromas, these lesions are considered as a single major criterion for TSC Roach et al, 1998). Oyerinde et al (2018) demonstrated in an observational cohort study that 39% of FCPs were found on the forehead, 31% on the scalp, 27% on the face (non-forehead), and 3% on the neck. FCPs typically occur on the forehead of TSC patients (Oyerinde et al, 2018).…”
Section: Facial Angiofibromas and Fibrous Cephalic Plaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Фиброзные бляшки имеют бежевый цвет, они шероховатые на ощупь и несколько выступают над окружающей кожей. Размер и число бляшек может варьировать [3,4,14,15,18].…”
Section: таблица 1 клинические диагностические критерии туберозного unclassified
“…Количество участков «шагреневой кожи» вариабельно, но чаще они бывают единичными. Размер их колеблется от 1 до 10 см и более [3,4,14,15,18].…”
Section: таблица 1 клинические диагностические критерии туберозного unclassified